Analysis of the relationship between knowledge management and quality management in the company Districarnazas Luna - Quintero, Andrés Mauricio Díaz (Universidad Santo Tomás / Instituto Colombiano de Normas Técnicas y Certificación ICONTEC, 2013)
On the prospect of knowing the relationships that have been established by entrepreneurial organizations between quality management systems (QMS) and knowledge management systems (KMS), arises the interest in analyzing the case of Districarnazas Luna, a company dedicate to the production and commercialization of cattle tanned hides.Theoretical frameworks that support the work lie on the developments regarding how knowlege is conceived in the organizations, as well as the perspectives, approaches, models and components of quality management and knowldge management.Districarnazas Luna has built an important wealth of knowledge, incorporating new technologies and expanding significantly; however, that does not respond to an intentional dynamic of building and transforming knowledge, since it occurs from the needs of the business, demands of the market, and not properly as a result of strategic plans to maintain a position of competitive advantage, which is why it is stressed the need to design strategies to move the uptake and implementation of practices aimed at creating a culture of knowledge in the company. It was analyzed what occurs in the organization and a model was outlined which aims at the articulation between quality management and knowledge management.